Applying The Ibadat Concept During A Natural Disaster - Muhammad Adib Samsudin; Mohammad Zaini Yahaya; Ahmad Munawar Ismail; Irwan Mohd Subri; Che Maryam Ahmad; Zainab Ismail; Illiyin Samsudin (Human Resource Management Academic Research Society, 2024)
Indexed by ERA